Value-adding of soft cheese from carabao's milk addition of pineapple - Ambayec, Maria Carmela Tonogbanua (1998)
Fresh soft cheese characterized by bits of pineapple mixed with the curd was developed to encourage more utilization of carabao's milk and the pineapple, and to make the native cheese or kesong puti more acceptable to the modern Filipino taste. The study was conducted in four phases. Phase I involved the determination of the best type of pre-treatment for the fresh pineapple that effectively inactivated the enzymes in the fruit. Heat treatment was found to be the most effective method. In Phase II, the most acceptable amount of pineapple in the cheese was determined through sensory evaluation of three cheese samples with varying amounts of heat-treated pineapple. In Phase III, results from the second phase were verified. In Phase IV, the physico-chemical properties of the product were compared to that without pineapple. The two samples were found to have significant difference with respect to texture and moisture content, but not in terms of pH, crude fat, and crude protein content.